ANALISIS INFORMASI KEUANGAN DALAM MENGEVALUASI KINERJA PEMERINTAH KABUPATEN DAIRI - Rimky Mandala Putra Simanjuntak; Sahala Purba; Erissa Antheresya Butar Butar (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2022)
This study aims to analyze the financial performance of local governments in terms of how many including: the Regional Financial Autonomy Scale, Fiscal Decentralization Amount, PAD Effectiveness, PAD Efficiency, Regional Fiscal Effectiveness, Regional Fiscal Efficiency, and BUMD Contribution Amount. This research is a quantitative descriptive study with the subject of research on regional financial information in Dairi Regency in 2013-2020, the data collection method used is the documentation method. The data analysis technique used is financial scale analysis. The results show that the Financial Autonomy Scale is still very low with an average value of 9.40%, Regional Financial Independence is very high with a value of 80.54%, and the amount of Fiscal Decentralization of 6.89% is categorized as very low. The effectiveness of PAD of 97.44% is included in the sufficient size. PAD efficiency in the group is very efficient with a value of 0.92%. Fiscal Effectiveness is 96.28% of a fairly effective measure. Regional Fiscal Efficiency with a value of 6.54% can be declared efficient. The amount of BUMD's contribution with a value of 13.23% is relatively low. The implications of this research as an evaluation for the regional/central government and the community in assessing the performance of the Dairi local government for the past 8 years are seen from several aspects.